Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 881 species occurrences available in GBIF matching the query: { "DatasetKey" : [ "is Moluscos Marinhos de Augusto Nobre" ] } The dataset includes 881 records from 1 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004349-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences